2022
DOI: 10.1172/jci157248
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell–derived microRNA-155 suppresses tumor progression via enhancing immune cell recruitment and antitumor function

Abstract: Evidence suggests that increased microRNA-155 (miR-155) expression in immune cells enhances anti-tumor immune responses. However, given the reported association of miR-155 to tumorigenesis in various cancers, a debate is provoked on whether miR-155 is oncogenic or tumor suppressive. We aimed to interrogate the impact of tumor miR-155 expression, particularly cancer cell-derived miR-155, on anti-tumor immunity in breast cancer. We performed bioinformatic analysis of human breast cancer databases, murine experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Utilizing publicly available TCGA data, Wang et al ( 7 ) confirmed that miR-155 levels are upregulated in breast cancer patients and positively correlated with overall patient survival ( Figure 1 ). Moreover, patients with stage I/II breast cancer and those without lymph node involvement had higher miR-155 levels than patients with advanced cancer stages and those with lymph node metastasis, respectively.…”
Section: Multifaceted Roles Of Mir-155mentioning
confidence: 88%
See 4 more Smart Citations
“…Utilizing publicly available TCGA data, Wang et al ( 7 ) confirmed that miR-155 levels are upregulated in breast cancer patients and positively correlated with overall patient survival ( Figure 1 ). Moreover, patients with stage I/II breast cancer and those without lymph node involvement had higher miR-155 levels than patients with advanced cancer stages and those with lymph node metastasis, respectively.…”
Section: Multifaceted Roles Of Mir-155mentioning
confidence: 88%
“…However, a critical question remains: Can we utilize the miRNAs to modulate immune function to address diseases affecting humans? To answer this question, Wang et al, in this issue of the JCI , have attempted to understand the antitumor role of one such oncomiR, miR-155, in breast cancer and its potential in harnessing the efficacy of immune checkpoint blockade (ICB) therapy ( 7 ).…”
Section: Mirnas At the Crossroads Between Inflammation And Cancermentioning
confidence: 99%
See 3 more Smart Citations